Role of immunotherapy in the treatment of advanced non-small-cell lung cancer. (January 2014) - Rijavec, Erika; Genova, Carlo; Alama, Angela; Barletta, Giulia; Sini, Claudio; Pronzato, Paolo; Coco, Simona; Bello, Maria Giovanna Dal; Savarino, Graziana; Truini, Anna; Boccardo, Francesco; Grossi, Francesco
ABSTRACT: After several decades of modest results with nonspecific immune stimulants, immunotherapy has become an exciting approach in the treatment of cancer. Although non-small-cell lung cancer has not been considered an immunogenic disease for very long, a better understanding of tumor immunology and the identification of new targets have led to the development of many clinical trials of immune-based therapies for this neoplasm. Promising results from many clinical trials suggest that immunotherapy could be an effective strategy in the management of advanced non-small-cell lung cancer. Further studies are required to help clinicians in the selection of patients who are more likely to benefit from immunotherapy strategies by the identification of biomarkers and to understand when the combination of immunotherapy with other agents should be recommended.